Quantitative Evaluation of the Impact of the Healthy Communities Initiative in Cincinnati - Mattke, Soeren (RAND Corporation, 2014)
Recently, large employers, health plans, and health care providers in the Cincinnati area joined with community organizations in an effort to improve health care and population health, as well as reduce health care costs. The resulting Healthy Communities Initiative in Cincinnati was implemented in 2009. In 2012, RAND Health Advisory Services assessed the Initiative's progress to date.